US Government Satcom Spending to Increase at a Steady Rate (Satellite Today, 2016)
While military spending on satcom is expected to grow at a rapid place, non-military spending is expected to be largely stagnant. The non-military portion of this market is focused on small applications and emergency backup, and is thus less bandwidth demanding than the military portion of the market. The majority of the North American market is non-military focused, thus, it is subject to less growth than other regions, such as the Middle East and Africa. Regions with the most political tension have the highest likelihood of requiring military satcom from the U.S. government.